A tale of two tells: dating the Çatalhöyük West Mound. (27th June 2018) - Orton, David; Anvari, Jana; Gibson, Catriona; Last, Jonathan; Bogaard, Amy; Rosenstock, Eva; Biehl, Peter F.
Abstract: Abstract : Çatalhöyük is one of the most well-known and important Neolithic/Chalcolithic sites in the Middle East. Settlement at the site encompasses two separate tell mounds known as Çatalhöyük East and West, with the focus of attention having traditionally been upon what is often regarded as the main site, the earlier East Mound. Limitations of dating evidence have, however, rendered the nature of the relationship between the settlements on these mounds unclear. Traditional models favoured a hiatus between their occupation, or, alternatively, a rapid shift from one site to the other, often invoking changes in natural conditions by way of an explanation. New dates challenge these theories, and indicate a potentially significant overlap between the occupation of the mounds, starting in the late seventh millennium BC.